(untitled) (Gestionar: revista de empresa y gobierno, 2022)
The forensic audit is a specialized tool that allows detecting and exposing fraud and corruption in the senior executive management of public entities known as "white collar crimes" with structures that are increasingly rooted and developed under various modalities and with the express intent to take advantage of and harm the state. However, in recent years in Peru, acts of corruption and functional misconduct by these executives have been increasingly detected and exposed, which greatly harm the budget allocated to meet the social demands of the population. In this line, the explanatory level research was carried out considering a sample of 323 individuals (active public officials) chosen in a non-probabilistic and non-random way with an unknown population. Through the survey and documentary review, information is shown related to the knowledge and importance of the forensic audit, the public spending executed in the years 2019 and 2020 and the economic damage detected by cases of corruption and functional misconduct in state entities. Among other results, it was found that the national government has a higher budget allocation with an annual execution of 90.8% in 2019 and 89.1% in 2020; likewise, local governments executed 69.4% and 63.4% in both periods respectively and regional governments executed 85.3% and 89.2% respectively; however, the economic damage due to corruption and functional misconduct detected by the Comptroller General of the Republic, reached its highest concentration in the transport and communications sector with 25% in 2019 and 16.5% in 2020, followed by the education sector. with 15.6% in 2019 and 14.5% in 2020 and finally the health sector with 16.2% in 2019 and 6.9% in 2020.